Child feeding practices and concerns: Thematic content analysis of Thai virtual communities. Issue 2 (30th November 2020) - Supthanasup, Abhirat; Banwell, Cathy; Kelly, Matthew; Yiengprugsawan, Vasoontara Sbirakos; Davis, Jenny L.
Abstract: Parents' child feeding practices are influenced not only by family but also by a broader circle of networks, including online groups. Peer‐to‐peer platforms such as Facebook groups facilitate a learning environment and may influence the transmission of user‐generated content into practice. These digital data not only benefit participants but also offer new opportunities for researchers to study related phenomena. Therefore, this study employs thematic content analysis to investigate peer‐exchanging discourse conveyed in Facebook peer‐support groups in children's diets in Thailand. To identify the area of interest, we classified and quantified the initial posts and investigated the relationship between initial posts' contents and community engagement. Thematic analysis was used to qualitatively describe the peer‐exchanging content that responded to the initial posts. Of the five approved Facebook groups, 200 initial posts with their 1964 comments were extracted anonymously. Results revealed that Facebook groups devoted to diets for children have become a platform for Thai parents to seek informational and emotional support. The top‐ranked initial posts were related to requesting knowledge and skills about age‐appropriate food and meal preparation. Parents have also expressed anxiety about feeding and tension related to food fussiness which created the need for emotional support. Age‐appropriate feeding, homemade baby foods, concerns about food seasonings and food allergy awareness were observable within online groups. However, a shift from traditional child feeding practices to new ideas created cultural gaps which lead to arguments in some families. Understanding these views would help guide to address parental concerns better.